Assessing and comparing the level of corporate integrity practices in Malaysian statutory bodies / Nurhidayah Yahya ... [et al.] - Yahya, Nurhidayah; Said, Jamaliah; Zakaria, Nor Balkish; Atan, Ruhaya (Accounting Research Institute (ARI), 2020)
There are few frauds and unethical cases in the Malaysian public sector and that might have contributed to the lower score in the Corruption Perception Index (CPI) for Malaysia. Hence corporate integrity is crucial as one of the mechanisms to curb corruption. This study aimed to evaluate and compare corporate integrity practices of federal and state statutory bodies through a survey questionnaire. The measurement for corporate integrity practices is based on three dimensions; ethical foundation, ethical culture and ethical risk management. Based on 194 responses received from the top management of Malaysian statutory bodies, the overall corporate integrity practices showed an above-average score of 5.938 for federal and 5.896 state statutory bodies. The T-test results indicated that there is no significant difference between corporate integrity practices in federal and state statutory bodies. Despite the different resources they have, both types of statutory bodies seem to have and instil an equally high level of corporate integrity practices.